Konflik Kelompok Puritanis dan Tradisionalis dalam NII (Negara Islam Indonesia) di Indonesia 1971-1992 M - M. Aziz Mukti; Irfan Zakariah (FIHROS: Jurnal Sejarah dan Budaya, 2024)
This research discusses the conflict that occurred between puritanical and traditionalist Islam in the Indonesian Islamic State (NII) from 1971 to 1992. In this research, it is clear that religious issues became a problem when salafiism entered the NII. There were two things that marked the entry of salafi ideology in NII. First, the formulation of the RMU tawhid designed by Aceng Kurnia. This tawhid took many opinions from Middle Eastern puritan figures such as Abu Ala Maududi and Sayyid Qutb. Second, the entry of Abdullah Sungkar and Abu Bakar Baasyir into the NII in 1972. Both had puritanical understandings and managed to gather followers into the NII. The conflict began when Abdullah Sungkar criticized NII Imam Ajengan Masduki for practicing TBC (Superstition, Bid'ah, and Khurafat) because of his religious understanding and following tarekat. The personal conflict between the two turned into a group conflict within NII. The incident caused a split between Ajengan Masduki's group and Abdullah Sungkar's group. Abdullah Sungkar and his followers declared their exit from NII in 1993. This research shows that there are conflicts that occur due to different understandings in the history of Indonesian Islamic radicalism.